(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2017)
يهدف هذا البحث إلى دراسة تأثير بعض منظمات النمو النباتية (الهرمونات النباتية) في إكثار بادرات من فول الصويا الصنف Sb-44متحملة للملوحة في الزجاج ( في المختبر ). تمّ إنبات البذور في أطباق بتري على وسط (MS) Murashinge and Skoog الصلب والمضاف إليه NaCl (100 ميلي مول/لتر) وBAP (6- بنزيل أمينو بيورين) (1 مغ/لتر) لمدة 10 أيام. تمّ عزل العقد الفلقية والبراعم القميّة من البادرات المتحمّلة للملوحة ومن ثم زرعت في الزجاج على وسط MS الصلب الذي يحوي NaCl (100 ميلي مول/لتر) وتراكيز مختلفة من BAP وNAA ( نفتالين حمض الخل ). تمّ الحصول على أعلى استجابة (71.42%) للعقد الفلقية وأفضل متوسط لعدد البراعم المتشكلة على هذه الأخيرة (3.20) على الوسط MS4 المضاف إليه BAP (1 مغ/لتر) + NAA (0.5 مغ/لتر). كانت أفضل نتيجة لعينات البراعم القمية التي أنتجت براعما ً68.57 % ، وأفضل متوسط لعدد البراعم المتشكلة بكل عينة 2.43 على الوسط MS2 الذي يحوي BAP (0.5 مغ/ل)+NAA (0.1 مغ/ل) . تمت استطالة البراعم وتجذيرها أيضاً على الوسط الشاهد MS بدون إضافة هرمونات نباتية وبنسبة 95% . نقلت البادرات المجذرة إلى أصص تحوي تورب، ورويت بماء ملحي(100 ميلي مول/لتر) وتمت أقلمتها في الشروط المخبرية. نمت معظم النباتات المتحملة للملوحة إلى مرحلة النباتات الكاملة بنسبة 80% خلال 13-14 أسبوعاً. The objective of this research is to study the effect of some plant growth regulators (plant hormones) on in vitro salt tolerant seedling multiplication. Seeds were germinated in Petri dishes on solid Murashinge and Skoog (MS) medium supplemented with NaCl (100 mM) and BAP (6-Benzylamino Purine) (1 mgŁ) for 10 days. Cotyledonary nodes and apical buds were isolated from salt tolerant seedling and cultured in vitro on solid MS medium containing NaCl (100 mMŁ) and different concentrations of BAP and NAA (Naphthalene acetic acid). The highest response (71.42%) of cotyledonary nodes (CN) and the best mean number of buds (3.20) formed per (CN) were obtained on medium with BAP (1 mgŁ) + NAA (0.5 mgŁ). The best result of apical buds explants producing buds 68.57% and the best mean number of buds per explant 2.43 were on medium with BAP (0.5 mgŁ) + NAA (0.1 mgŁ). buds were elongated, as well as rooted on control MS medium without plant hormones with 95%. The rooted plantlets were transfered into pots with soil, irrigated with saline water (100 mMŁ) and acclimatized at laboratory conditions. Most salt tolerant plants grew to maturity with 80% in 13-14 weeks.